Laboratorio virtual de entrenamiento SAP Hybris (2021)
ABSTRACT: One of the most complicated steps in learning curves of new technologies usually is the beginning of the learning process. It’s hard to learn something new and even more when you give the first steps towards more advanced concepts. Hence the importance of having good documentation, with detailed steps to follow and a solution to common problems. The problem is that many times this information is hard to find because of lack of documentation, wrong documentation or the lack of tutorials on the subject. Which makes people lose time making them ask constant questions to their superiors, this makes them lose valuable time in the learning process. Because of this they take the decision of documenting the self learning of SAP Hybris and at the same time the elaboration of a guide for the future new trainees in the company so they can learn the basic needs to manage the SAP Hybris technology.